Implementation of the Supervision Function on Public Sector Employees (Study at PT. PLN's South Sulawesi, Southeast Sulawesi and West Sulawesi Regions) - Rivai, Nur Ilmiah (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
Good supervision is needed at the Office of PT. PLN (Persero) in the South Sulawesi, Southeast Sulawesi and West Sulawesi Regions so that employees can work effectively and produce optimal work. The purpose of this study, is to analyze the supervisory function carried out at PT. PLN (Persero) South Sulawesi, Southeast Sulawesi and West Sulawesi Regions. This research method uses quantitative research with descriptive research type. Data collection techniques using questionnaires in the form of a checklist and using descriptive analysis techniques. The results of the study showed that the direct supervision conducted was quite good, while the direct supervision was quite good.